THE PROCESS OF TRAINING TEACHERS OF TECHNOLOGY EDUCATION IN THE CONTEXT OF THE INTRODUCTION OF DIGITAL TECHNOLOGIES INTO EDUCATION (Web of Teachers: Inderscience Research, 2024)
The article highlights the problems of the learning process of teachers of technological education at the level of the introduction of digital technologies into education, as well as some considerations on how to solve it.